2023
DOI: 10.1126/sciadv.adh0480
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-like geometry as an evolutionary response to predation?

Abstract: Fractal-like, intricate morphologies are known to exhibit beneficial mechanical behavior in various engineering and technological domains. The evolution of fractal-like, internal walls of ammonoid cephalopod shells represent one of the most clear evolutionary trends toward complexity in biology, but the driver behind their iterative evolution has remained unanswered since the first hypotheses introduced in the early 1800s. We show a clear correlation between the fractal-like morphology and structural stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…For example, FEA has indicated that increased septal complexity results in increased principal stress on the septa but increased the tolerance to point loads, which mimic biting forces from known predators [15,19]. Thus, predation rather than tolerance to hydrostatic pressure may have shaped the evolution of increased septal complexity [20], which complicates interpretations of the relationship between shell form and bathymetry in either relative or absolute terms. Using similar FEA methodologies and in contradiction to previous findings, more septal folds have also been found to decrease the principal stress on individual septa [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, FEA has indicated that increased septal complexity results in increased principal stress on the septa but increased the tolerance to point loads, which mimic biting forces from known predators [15,19]. Thus, predation rather than tolerance to hydrostatic pressure may have shaped the evolution of increased septal complexity [20], which complicates interpretations of the relationship between shell form and bathymetry in either relative or absolute terms. Using similar FEA methodologies and in contradiction to previous findings, more septal folds have also been found to decrease the principal stress on individual septa [16].…”
Section: Introductionmentioning
confidence: 99%